Human Research Ethics Committee Experiences and Views About Children's Participation in Research: Results From the MESSI Study. (February 2022) - Taplin, Stephanie; Chalmers, Jenny; Brown, Judith; Moore, Tim; Graham, Anne; McArthur, Morag
As part of a larger study, Australian Human Research Ethics Committee (HREC) members and managers were surveyed about their decision-making and views about social research studies with child participants. Responses of 229 HREC members and 42 HREC managers are reported. While most HREC members had received ethical training, HREC training and guidelines specific to research involving children were rare. Most applications involving children had to go through a full ethical review, but few adverse events were reported to HRECs regarding the conduct of the studies. Revisions to study proposals requested by HRECs were mostly related to consent processes and age-appropriate language. One-third of HREC members said that they would approve research on any topic. Most were also concerned that the methodology was appropriate, and the risks and benefits were clearly articulated. Specific training and guidance are needed to increase HREC members' confidence to judge ethical research with children.